Effect of pulsed radiofrequency therapy on the suprascapular nerve in shoulder pain of various aetiology - Gabrhelík, Tomáš; Michálek, Pavel; Adamus, Milan; Mikova, M; Doleček, Libor (Irish journal of medical science, 2010)
BACKGROUND: Pulsed radiofrequency treatment (PRF) applied to the suprascapular nerve may provide pain relief for patients suffering from shoulder pain as described in three case series. AIMS: The effect of PRF to the suprascapular nerve was retrospectively analysed on 28 patients with shoulder pain lasting longer than 1 month, with a 6-month follow-up. Group A was treated with PRF and local anaesthetics only while group B was treated with PRF, local anaesthetic and steroid. Pain scores were evaluated before and after the procedure and at 1, 3 and 6 months. RESULTS: More than 50% of patients in both groups had significant pain relief after 3 months. No major, but only one minor complication occurred. CONCLUSIONS: Our results suggest that the analgesic effects of PRF last more than 3 months in the majority of patients. The addition of steroid to the PRF treatment appears to have no benefit.
Keywords: dospělí; Female; Pain Measurement; Shoulder; Nerve Block; Adult; ženské pohlaví; lidé; nervová blokáda; měření bolesti; Shoulder Pain; retrospektivní studie; Male; Aged; rameno; bolest ramene; lidé středního věku; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; Humans